VITA IGNATII LOIOLAE ET RERUM SOCIETATIS IESU - Polanco, Juan Alfonso de (MONUMENTA HISTORICA SOCIETATIS IESU, 1894)
CONTENIDO: V.1. 1491-1549 -- V.2. 1550-1552 -- V.3. 1553-1554 -- V.4.1554 -- V.5. 1555 -- V.6. 1556